The Influence of Transformational Leadership in Organizations: The Mediating Role of Meaningful Work - Özgür Demirtaş; Durdu Mehmet Biçkes; Serdar Yener; Mustafa Karaca (Journal of Economy Culture and Society)
A leader is a person who has the potential to mobilize individuals who want to struggle for common goals and shared aspirations. Leaders have some key roles in achieving organizational goals. Today, change and transformation occur much faster than in the past. Particularly in parallel with technological innovations, this change is an important factor in making parallel innovations when organizations continue their sustainable competitive advantages. For this reason, the roles of leaders, which are the most important driving forces of the organizations, in this change and transformation are more important than the role models. In this context, this study aims to investigate the effects of organizational citizenship behaviors, unethical organizational behaviors, and the effects of integration on work. In addition, the mediating role of job meaning in the process has been examined. It has been found that current work findings and transformational leaders are influential in work integration and organizational citizenship behaviors, and also act as a partial means of making meaningful work in the model.